2011
DOI: 10.1177/1741826711418165
|View full text |Cite
|
Sign up to set email alerts
|

Is there a BP benefit of changing the time of aspirin administration in treated hypertensive patients?

Abstract: It does not appear useful to advise patients with long-standing hypertension to modify timing of aspirin intake in order to reduce BP values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The search strategy identified 4,272 records; 28 studies were eligible for inclusion and informed the analysis (see Figure ). Twelve studies investigated the effects of aspirin when administrated once‐daily in the morning / after awakening vs. in the evening / at bedtime; 12 studies compared aspirin administration once‐daily with two or more times daily; and four studies compared once‐daily vs. alternate‐day (or less frequent) aspirin dosing. Table shows the main study characteristics.…”
Section: Taxonomy Of Studies Assessing Aspirin Regimens' Effectivenessmentioning
confidence: 99%
See 4 more Smart Citations
“…The search strategy identified 4,272 records; 28 studies were eligible for inclusion and informed the analysis (see Figure ). Twelve studies investigated the effects of aspirin when administrated once‐daily in the morning / after awakening vs. in the evening / at bedtime; 12 studies compared aspirin administration once‐daily with two or more times daily; and four studies compared once‐daily vs. alternate‐day (or less frequent) aspirin dosing. Table shows the main study characteristics.…”
Section: Taxonomy Of Studies Assessing Aspirin Regimens' Effectivenessmentioning
confidence: 99%
“…In 9/12 studies, 24‐hour or 48‐hour mean ambulatory blood pressure measurements (ABPM) were reported . Of those, four parallel RCTs conducted by the same research group favored aspirin administration in the evening, with most results being statistically significant (see Figure ).…”
Section: Taxonomy Of Studies Assessing Aspirin Regimens' Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations